Brief Report: State‐Level Number of Physically Inactive US Adults With Arthritis Who can Improve Their Anxiety and Depression by Exercising. Issue 2 (6th January 2020) - Kelley, George A.; Kelley, Kristi S.; Callahan, Leigh F.
Abstract : Objective: Provide state‐level estimates of the number of physically inactive adults in the United States with arthritis and other rheumatic and musculoskeletal diseases (RMDs) who could improve their anxiety and depression by exercising. Methods: Utilizing 1) number‐needed‐to treat (NNT) data from two prior meta‐analyses of randomized controlled trials addressing the effects of exercise on anxiety and depression in adults with arthritis and other RMDs, 2) recent state‐level prevalence estimates on arthritis and physical inactivity in adults with arthritis and other RMDs, and 3) state‐level 2010 US Census population data, the number of physically inactive adults with arthritis and other RMDs who could improve their anxiety and depression by exercising was estimated. Results: Across all states and the District of Columbia, the number of adults with arthritis and other RMDs who could improve their anxiety and depression by starting an exercise program was estimated at 3 433 167 (95% confidence interval [CI] = 3 171 000‐3 703 522) for anxiety and 2 942 706 (95% CI = 2 718 000‐3 174 438) for depression. For anxiety, numbers ranged from 3677 (95% CI = 3235‐4154) in the District of Columbia to 271 253 (95% CI = 243 998‐298 508) in Texas. For depression, numbers ranged from 3151 (95% CI = 2773‐3561) in the District of Columbia to 232 502 (95% CI = 209 140‐255 863) in Texas. Conclusion: These state‐specific data suggest that a large number of physically inactive US adults with arthritis and other RMDs could improve their anxiety and depression by starting and maintaining a regular exercise program.